Association Between Long-term Functional Outcome and Change in hs-CRP Level in Patients With Acute Ischemic Stroke. Issue 5 (September 2020) - Lee, Sujin; Song, In-Uk; Na, Seung-Hee; Jeong, Du-Shin; Chung, Sung-Woo
Abstract : Background and Purpose: Elevated high-sensitivity C-reactive protein (hs-CRP) has been suggested as a risk factor for ischemic stroke. However, the predictive value of hs-CRP for long-term outcomes is poorly defined. Therefore, we conducted this study to evaluate whether change in hs-CRP level plays a role in the prognostic value of long-term functional disability. Methods: We studied 263 patients with acute ischemic stroke and 104 healthy controls (67.5±11.26 and 68.17±11.21 y, respectively). hs-CRP was measured on admission and on the seventh day of hospitalization. The patients were classified into 2 groups on the basis of difference in hs-CRP level from admission to the seventh day of hospitalization (group 1, hs-CRP on admission>the seventh hospital day; group 2, hs-CRP on admission<the seventh hospital day). The correlation between change in hs-CRP level and functional disability using the modified Rankin Scale score (mRS) at 1, 3, 6, and 12 months after stroke onset was analyzed. Results: We observed significant differences between initial hs-CRP level in all patients (0.96±2.82 mg/dL) and healthy controls (0.34±0.71 mg/dL, P =0.029). Significant differences in mRS at the 4 different timepoints was not observed between 2 groups ( P =0.453, 0.225, 0.229, and 0.396, respectively). The Spearman rank-order correlation coefficients showed that change in hs-CRP level increasingly differed over time and was statistically correlated with mRS (coefficient/ P : at 1 mo, 0.139/0.024; at 3 mo, 0.149/0.015; at 6 mo, 0.147/<0.001; and at 12 mo, 0.134/0.03). However, the results were very low correlation coefficients, despite their statistical significance. Conclusion: This study did not clearly show an association between increase in hs-CRP level over time and long-term functional disability.